Uso del tapabocas y relación con la halitosis en los estudiantes de odontología de la Universidad Antonio Nariño Sede-Neiva (2021)
Having a good oral hygiene when wearing a mouthguard helps to reduce some pathologies that manifest with halitosis, among which are digestive and respiratory disorders. Bad breath is an indicator of oral microbial imbalance, product of poor aeration and deficient oral hygiene.